2013
DOI: 10.1039/c3an00716b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric relative humidity on Stratum Corneum structure at the molecular level: ex vivo Raman spectroscopy analysis

Abstract: Skin hydration plays an important role in the optimal physical properties and physiological functions of the skin. Despite the advancements in the last decade, dry skin remains the most common characteristic of human skin disorders. Thus, it is important to understand the effect of hydration on Stratum Corneum (SC) components. In this respect, our interest consists in correlating the variations of unbound and bound water content in the SC with structural and organizational changes in lipids and proteins using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
156
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(162 citation statements)
references
References 74 publications
5
156
1
Order By: Relevance
“…material). Generally, our Raman assignments correlate with those in the literature [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The Raman spectrum of the SC is dominated by vibrational bands of its structural proteins, lipids, and tissue water.…”
Section: Resultssupporting
confidence: 86%
“…material). Generally, our Raman assignments correlate with those in the literature [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The Raman spectrum of the SC is dominated by vibrational bands of its structural proteins, lipids, and tissue water.…”
Section: Resultssupporting
confidence: 86%
“…The changes of the lipid structure of the stratum corneum subsequent to interaction with water have already been described by different work groups [29,49,50]. Such lipid changes could also occur when the petrolatum is topically applied to the skin as this induces a swelling effect in the stratum corneum.…”
Section: Discussionmentioning
confidence: 93%
“…CRS can help gain a better understanding of moisturizers' mechanisms within the skin through the direct measurement of water content, distribution and SC swelling [35]. In addition, it has been recently demonstrated that CRS can differentiate between different water-binding states, including unbound, partially bound and primary bound water [68,69]. The water content in each binding state has been found to vary differently in function of external stimuli, such as humidity and mechanical stress and, remarkably, correlations with structural and organizational changes in lipids and proteins were highlighted [68,70].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been recently demonstrated that CRS can differentiate between different water-binding states, including unbound, partially bound and primary bound water [68,69]. The water content in each binding state has been found to vary differently in function of external stimuli, such as humidity and mechanical stress and, remarkably, correlations with structural and organizational changes in lipids and proteins were highlighted [68,70]. This demonstrates the potential of CRS to study the correlation of the skin barrier and hydration status in function of different stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation